PENGARUH INFUS RIMPANG TEMULAWAK (Curcuma xanthorrhiza) TERHADAP KADAR HEMOGLOBIN DAN JUMLAH ERITROSIT TIKUS PUTIH YANG DIBERI LARUTAN TIMBAL NITRAT [(PbNO3)2] - Sugiharto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
The purpose of this experiment was to study the effect of turmeric (Curcuma xanthorrhiza) rhizome infuse to hemoglobin concentration and number of erythrocyte of [(PbNO3)2] treated rats. Pb was presumed to be link at sulphyhydril groups that may caused an inhibition to several enzymatic process, such as d-ALAD and heme sintetase which is caused the inhibits of Hb synthesis and erythropoesis. Twenty female rats was used in this experiment. They were divided into five groups, i.e. (A) control (treated with 1 ml aquadest); (B) treated with 1/2 ml of 12 ppm lead solution and 1/2 ml aquadest; (C) treated with 1/2 ml of 12 ppm lead solution and 1/2 ml of 20% turmeric rhizome infuse; (D) treated with 1/2 ml of 50 ppm lead solution and 1/2 ml aquadest; (E) treated with 1/2 ml of 50 ppm lead solution and 1/2 ml of 20% turmeric rhizome infuse. The treatment was given orally every day (30 days) using a modified syringe. After 30 days of treatment, the blood sample were taken about 2 ml by heart puncture. The Hb concentration was determined using by Cyanmethemoglobin method and number of erythrocyte was counting on Haemocytometer Improved Neubauer. Data were analyzed by Anova and LSD test (α = 0.05). The results of this study shows that 20% of turmeric rhizome infuse statistically has a significant effect (P < 0.05) to increasing of hemoglobin concentration but hasn’t significant to prevent the number of erythrocyte decreasing of [(PbNO3)2] treated.